Manhaj Fiqh Salafi-Literal Eksplorasi, Kritik dan Apresiasi - Miftahul Huda (Ulumuna, 2015)
In the midst of various thoughts and applications of sharī‘ah in social life, and due to the historical momentum in nowadays, the method (manhaj) of literal-salafī is one of the most highlighted, appreciated and criticized aspects, both in theoretical and practical perspectives. This article is aimed to explore and describe systematically some aspects of such a method and then put them on the critical analysis framework in the epistemological and sociohistorical perspectives. Such a method has really its own superiorities and attraction in certain aspects, especially in theological and ideological views. That is due to the more consistent reference to the main sources of Islamic law, the Qur’an and the Sunnah. But in another side, there are weaknesses that should not be ignored, both in epistemological and sociological view. Those weaknesses have really been existed in its fundamental paradigms, doctrines, and also because such a manhaj has not yet been sufficiently developed in detail and practical concepts. DOI: http://dx.doi.org/10.20414/ujis.v19i1.1253